Application of NIR to determine effects of hydrocarbon microseepage in oil palm vegetation stress - Jamaludin, M.I. (IEEE Computer Society, 2015)
The dynamism of health vegetation could be affected by oil leakage such phenomena of hydrocarbon microseepage from. This effect can alter a plant's physical growth and reflectance spectra for detecting potential oil reservoir in the field. Hyperspectral remote sensing technology tool has an effective and monitor vegetation health in potential onshore reservoir areas. This paper investigates the potential for using NIR analysis to study the impacts of hydrocarbon seepage on the oil palm tree. In this application, 40 trees were stimulated with hydrocarbon microseepage and remaining 10 trees were left as control. The reflectance spectral data were collected by using ASD FieldSpec 4 Standard-Res spectroradiometer with a range of 350-2500 nm. Therefore, the observations of samples were taken at least 90 spectral from each tree. All the spectra was preprocessed and averaged until becoming 18 spectra for each of the samples. The spectra acquisition was taken on the first day, day 60th and day 90th of plantation. However, the comparative physical appearance of the tree and reflectance spectra between the three data acquisition was analysed in red-edge, visible, and 1st derivative to determining the effects of hydrocarbon microseepage. The result indicated that 30 oil palm trees with more than 40 crude oil were dying. The trees with 10 hydrocarbon microseepage were experienced mild stressed based from the spectral trends at day 60 and day 90 reflectance spectral. While 1st derivative shows that the red-edge positions was shifted to blue spectral which is indicating vegetation stress. Â© 2015 IEEE.